الحج ومساهمته في تنمية أسس التنمية البشرية - الخضراوي, هشام (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
: This paper discusses the roots of Al-Hajj and its direct influence on the human development, it appears that all the nations that approved the ritual of Hajj were for the purpose of developing and renewing the capabilities of the individual in certain places and times with the aim of unburden him of the monotony of place and time, and accustom him to dealing with different individuals as well as adapting to an environmental climate and different cultures, including the development of several physical and spiritual aspects that cannot be taught otherwise.This paper follows the comparative-analytical historical approach, moreover, the analysis of historical events alone with regard to the ritual of Hajj among Muslims and its relationship to human development without referring to Hajj in other religions makes the research incomplete, and thus its extension throughout history, and since the first Those who performed Hajj were the angels, Prophet Adam, lastly other nations, it was necessary limit to the comparison between the Hajj among Muslims and the Jews, due to the convergence of time between them, as well as the similarities. According to the literature review, the paper concluded that Hajj develops several physical and spiritual aspects that cannot be taught otherwise, improves planning and goal, encourages completing a specific work in a predetermined, improves the ability to achieve a positive result, urges cooperation and teaches patience, develops the individual's physical and intellectual abilities, unburdens from the monotony of place and time.